Pengaruh Hasil Belajar Micro Teaching dan Lingkungan Keluarga Terhadap Minat Menjadi Guru Akuntansi Melalui Efikasi Diri Sebagai Variabel Moderasi - Denandhia Arvina Karyantini; Rochmawati Rochmawati (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
Teacher is the main factor determain the success of education. Professional teachers are needed to achieve these goals. One of the requirements to become a professional teacher is to take an undergraduate education program. However, not all students at State University of Surabaya who take the accounting study program have an interest in becoming an accounting teacher. This is because interest in becoming a teacher can be influenced by encouragement from oneself and strengthened by external factors that come from outside. This study aims to analyze the influence of micro teaching learning outcomes to the interest in becoming an accounting teacher, the influence of the family environment on the interest in becoming an accounting teacher, the effect of micro teaching learning outcomes through self-efficacy on the interest in becoming an accounting teacher, and the influence of the family environment through self-efficacy on the interest in becoming an accounting teacher. The type of ex-post-facto quantitative research. This study has a population 112 students of the Accounting Education, Faculty of Economics and Business, State University of Surabaya. The sampling method was purposive sampling. The sample was determind based on the Slovin formula amounted to 88 students. The data collection was carried out through a likert scale questionnaire which hasben tasted for validity and reability. The result of data analysis using path analysis showed there are micro teaching learning outcomes positively and significantly able to be influenced interest in becoming an accounting teacher, family environtment able to be influenced interest in becoming an accounting teacher positively and significantly, self-efficacy unable moderate of micro teaching learning outcomes on the interest in becoming an accounting teacher, and unable moderate the family environment on the interest in becoming an accounting teacher.